Analisis Rasio Keuangan Untuk Mengukur Kinerja Keuangan Pada PT. PP Londom Sumatra Indonesia Tbk (Lonsum) Periode 2018 - 2022 - Nur Aisyah; Nurman Nurman; Hety Budiyanti; Uhud Darmawan; Andi Mustika Amin (Institut Teknologi dan Bisnis (ITB) Semarang, 2024)
Financial performance is useful for gaining insight into the entity's financial health, evaluating operational performance, identifying trends, and making decisions based on relevant financial information. In measuring financial performance, you can use liquidity ratios, profitability ratios, solvency ratios, activity ratios and market ratios to identify potential areas that need to be improved or are indicated as problematic. This research aims to determine the financial performance of PT. PP London Sumatra Tbk in 2018-2022. The variables of this research are financial performance, liquidity ratios, profitability ratios, solvency ratios, activity ratios and market ratios. The population and sample of this research are financial reports from PT. PP London Sumatra Tbk 2018-2022. Data collection was carried out using documentation techniques. The results of this research indicate that the financial performance of PT. PP London Sumatra Tbk for 2018-2022 based on industry standards using liquidity ratios, profitability ratios, and solvency ratios and activity ratios are classified as very good. Meanwhile, the financial performance of PT. PP London Sumatra for 2018-2022 based on industry standards using market ratios is classified as not good.